2021
DOI: 10.3389/fonc.2021.731503
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Tumor Hypoxia With Radionuclide-Labeled Tracers for PET

Abstract: The hypoxic state in a solid tumor refers to the internal hypoxic environment that appears as the tumor volume increases (the maximum radius exceeds 180-200 microns). This state can promote angiogenesis, destroy the balance of the cell’s internal environment, and lead to resistance to radiotherapy and chemotherapy, as well as poor prognostic factors such as metastasis and recurrence. Therefore, accurate quantification, mapping, and monitoring of hypoxia, targeted therapy, and improvement of tumor hypoxia are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 181 publications
(178 reference statements)
0
35
0
Order By: Relevance
“…In this review, we describe dual-mode imaging methods reported for the ability to characterize hypoxia-relevant characteristics reported since the year 2000. For reviews of single-mode detection of hypoxia, readers are referred elsewhere [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. This article is divided into two introductory sections—characteristics of oxidative stress and hypoxia that can be imaged and imaging modalities used to study hypoxia—followed by descriptions of dual-modality imaging of hypoxia using cocktails of probes in combination with multiple imaging modalities and then dual-modality imaging of hypoxia with multimodal probes for multiple imaging modalities.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we describe dual-mode imaging methods reported for the ability to characterize hypoxia-relevant characteristics reported since the year 2000. For reviews of single-mode detection of hypoxia, readers are referred elsewhere [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. This article is divided into two introductory sections—characteristics of oxidative stress and hypoxia that can be imaged and imaging modalities used to study hypoxia—followed by descriptions of dual-modality imaging of hypoxia using cocktails of probes in combination with multiple imaging modalities and then dual-modality imaging of hypoxia with multimodal probes for multiple imaging modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Most clinically tested radiotracers for PET imaging of hypoxia represent 18 F-labeled 2-nitro-imidazoles. Several excellent reviews have summarized the chemistry and application of PET radiotracers, emphasizing 2-nitroimidazoles for imaging hypoxia (Fleming et al 2015 ; Wuest and Wuest 2013 ; Huang et al 2021 ). Nitroimidazoles enter cells by passive diffusion followed by their reduction to nitro radical anions, which are further reduced to nitroso- and hydroxylamine compounds in the presence of hypoxic conditions leading to intracellular trapping (Mees et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been ongoing interest in developing more specific radiotracers, including radiotracers that target other transporter proteins for nutrients associated with metabolic processes or radiotracers targeting specific signatures expressed in tumor cells. Additionally, hypoxia is one of the leading reasons for treatment failure, so identifying hypoxic regions would be beneficial for patient care [ 5 , 6 ]. Some notable examples are 3′-deoxy-3′[ 18 F]fluorothymidine ([ 18 F]FLT) for monitoring nucleoside transporters/cell proliferation, [ 18 F]FAZA and [ 18 F]FMISO for identifying regions of hypoxia, 68 Ga-NOTA-bombesin derivatives for imaging prostate cancer by targeting gastrin-releasing peptide receptors (GRPR), and many others [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%